2021
DOI: 10.1016/j.envpol.2020.115714
|View full text |Cite
|
Sign up to set email alerts
|

Assessing correlations between short-term exposure to atmospheric pollutants and COVID-19 spread in all Italian territorial areas

Abstract: The spread of SARS-CoV-2, the beta coronavirus responsible for the current pneumonia pandemic outbreak, has been speculated to be linked to short-term and long-term atmospheric pollutants exposure. The present work has been aimed at analyzing the atmospheric pollutants concentrations ( PM 10 , PM 2.5 , NO 2 ) and spatio-temporal distribution of cases and deaths (specifically incidence, mortality and lethality ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 34 publications
(68 reference statements)
3
38
0
1
Order By: Relevance
“…The authors found an increase of 2.24% (95% CI 1.02–3.46) and 1.76% (95% CI 0.89–2.63) in the daily counts of Covid-19 confirmed cases for an increase of 10-μg/m 3 (at cumulative lag of 0 -14 days) in PM 2.5 and PM 10 , respectively 22 . Similar results were found at the Province level in Italy by several authors 23 , 28 , 29 . In contrast, in 28 geographical areas of Japan 26 , the epidemic growth (as cumulative count of confirmed cases over a period March—6 April 2020) was not found statistically associated with PM 2.5 (and other pollutants), after adjusting for demographic variables.…”
Section: Discussionsupporting
confidence: 89%
“…The authors found an increase of 2.24% (95% CI 1.02–3.46) and 1.76% (95% CI 0.89–2.63) in the daily counts of Covid-19 confirmed cases for an increase of 10-μg/m 3 (at cumulative lag of 0 -14 days) in PM 2.5 and PM 10 , respectively 22 . Similar results were found at the Province level in Italy by several authors 23 , 28 , 29 . In contrast, in 28 geographical areas of Japan 26 , the epidemic growth (as cumulative count of confirmed cases over a period March—6 April 2020) was not found statistically associated with PM 2.5 (and other pollutants), after adjusting for demographic variables.…”
Section: Discussionsupporting
confidence: 89%
“…Several studies previously investigated on the association between air pollution and Covid-19 spread and adverse outcomes in Italy [ 4 , 8 , 10 , 11 , 13 15 , 29 , 30 , 35 , 36 , 40 , 44 , 46 ]. A study by Conticini and colleagues focused on two Northern Italy Regions, Lombardy and Emilia Romagna, which are part of the Padan plain.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies (as shown in Table S1 ) critically investigated lockdown effects toward concentrations of air pollutants ( Abdullah et al., 2020 ; Nakada and Urban, 2020 ; Tanzer-Gruener et al., 2020 ; Tobías et al., 2020 ; Venter et al., 2021 ; Yuan et al., 2021 ); air pollution relationship with COVID-19 cases ( Accarino et al., 2021 ; Tello-Leal and Macías-Hernández, 2020 ); meteorology and air pollutants changes ( Hossain et al., 2021 ; Sulaymon et al., 2021 ); traffic and mobility changes ( Aloi et al., 2020 ); and the application of statistical and modelling ( Bao and Zhang, 2020 ; He et al., 2020 ; Liu et al., 2020b ) while this study focuses mainly on air pollutants effects in cities with the analysis related to population exposure to non-carcinogenic risks. The COVID-19 pandemic affected human activities, primarily when the MCO was implemented to reduce the chain of infection among the population in Malaysia.…”
Section: Introductionmentioning
confidence: 99%